Relationship between the body mass index and the ponderal index with physical fitness in adolescent students - Marco Cossio-Bolaños; Rubén Vidal- Espinoza; Camilo Urra Albornoz; José Fuentes-Lopez; Lucila Sánchez-Macedo; Cynthia Lee Andruske; José Sulla-Torres; Rossana Gómez Campos (BMC Pediatrics, 2022)
Abstract Background The relationship between the Body Mass Index (BMI) with physical fitness in children and adolescent populations from diverse regions are consistent. However, the relationship between the Ponderal Index (PI) with physical fitness, based on what is known to date, has not been examined in depth. The objective was to evaluate the relationships between BMI and PI with three physical fitness tests of students living at moderate altitudes in Peru. Methods A descriptive correlational study was carried out with 385 adolescents, between the ages of 10.0 to 15.9 years old, from the province of Arequipa, Peru. Weight, height, and three physical fitness tests (horizontal jump, agility, and abdominal muscle resistance) were evaluated. BMI and PI were calculated, and they were, then, categorized into three strata (low, normal, and excessive weight). Specific regressions were calculated for sex, using a non-lineal quadratic model for each item adjusted for BMI and PI. Results The relationship between BMI and PI with the physical tests reflected parabolic curves that varied in both sexes. The regression values for BMI in males oscillated between R2 = 0.029 and 0.073 and for females between R2 = 0.008 and 0.091. For PI, for males, it varied from R2 = 0.044 to 0.82 and for females, from R2 = 0.011 to 0.103. No differences occurred between the three nutritional categories for BMI as well as for PI for both sexes (p range between 0.18 to 0.38), as well as for low weight (BMI vs PI), normal weight (BMI vs PI), and excessive weight (BMI vs PI) (p range between 0.35 to 0.64). Conclusions BMI showed inferior quadratic regressions with respect to the PI. In addition, physical performance was slightly unfavorable when it was analyzed by BMI. PI could be a useful tool for analyzing and predicting physical fitness for adolescents living at a moderate altitude since it corrects for the notable differences for weight between adolescents.